Nox formation in fixed-bed biomass combustion: Chemistry and modeling. (15th April 2021) - Ma, Wenchao; Ma, Chen; Liu, Xu; Gu, Tianbao; Thengane, Sonal K.; Bourtsalas, Athanasios; Chen, Guanyi
Highlights: A detailed model for nitrogen species formation during MSW incineration is established. A comprehensive nitrogen formation mechanism is described quantitatively. The particle size with the lowest NO production is 3 mm. High initial temperature can accelerate N2 O from 6.3 × 10 −12  ppmv to 3.0 × 10 −10  ppmv. Abstract: The renewable and carbon neutral nature of biomass makes it an alternative clean energy resource. However, NOX emission during biomass combustion, a widely used approach for extracting energy from biomass, poses serious environmental concerns. A fundamental investigation of nitrogen species formation mechanism during biomass combustion is important to minimize NOX and nitrous oxide emissions. In this study, a comprehensive computational fluid dynamics (CFD) model that combines nitrogen chemistry with flow and combustion simulations is presented. We call this model BASIC: bulk accumulated solids incineration code. BASIC combined sub-models for drying, devolatilization, volatiles combustion, and char oxidation, nitrogen chemistry, and conservation equations. The model is first validated against data on fixed bed combustion of biomass from literature. Results show that particle size and the initial temperature have significant impact on NO and N2 O formation, whereas pressure shows a less significant effect. NOX formation mechanism pathways show that the oxidation of ammonia has a significant influence on NO production, while the reduction of NO by surface dominated hydrogen play an important role in reducing its concentration in the gas phase. Net N2 O formation is determined both by the reactions of precursors with NO and the process of N2 O decomposition to N2 . Unlike prior CFD models, BASIC can predict not only N2 O formation for biomass combustion, an important greenhouse gas, but also optimal parameters, e.g., particle size and temperature, for the lowest NOX production.